Paham Ketuhanan dalam Kepercayaan Dewi Ibu (Đạo Mẫu) pada Masyarakat Adat di Vietnam - Huy Quốc Lã; Desima Erlinda Agnesia Sitorus; Leo Agung Tyas Prasaja; Agus Widodo (Fakultas Teologi, Universitas Sanata Dharma, 2025)
There are many religions and beliefs in the world. Among them, we must mention five major religions such as Christianity, Hinduism, Islam, Judaism and Buddhism. Besides these major religions, other religious beliefs still exist, namely the Đạo Mẫu Belief, Thờ Kính Tổ Tiên Belief (ancestor worship belief), Thờ Trời Belief, and others. These beliefs often originate from local cultures. Although belief is not as universal and strong as religion, it is imbued with the characteristics and identity of indigenous people's belief in a Supreme Being. In this article, the writer will clarify the identity of indigenous people's belief in their own beliefs, specifically the Mother Goddess belief (Đạo Mẫu) of the Vietnamese people. This study also focuses on the belief in divinity in the Đạo Mẫu traditional belief. Using the library research method, the writer traces official sources of information through books, articles, and etc to give an overview of the Mother Goddess belief. Specifically, this article will present the origins of the formation of the Đạo Mẫu belief and also mention the divine system in the Đạo Mẫu belief. Apart from that, the author presents the unique rituals in the Mother Goddess belief, as well as the meaning of these rituals. Finally, the researcher will explain the views and role of the Mother Goddess in the Đạo Mẫu Belief.AbstrakAda banyak kepercayaan dan agama di dunia, diantaranya lima agama besar seperti Kristen, Hindu, Islam, Yudaisme, dan Budha. Selain agama-agama besar tersebut, masih ada kepercayaan lain yang berasal dari budaya lokal yaitu Kepercayaan Đạo Mẫu, Kepercayanan Thờ Kính Tổ Tiên (kepercayaan pemujaan leluhur), Kepercayaan Thờ Trời, dan lain lain. Meski kepercayaan ini tidak bersifat universal dan sekuat agama, namun kepercayaan tersebut dijiwai dengan ciri dan identitas kepercayaan adat terhadap Yang Maha Esa. Dalam artikel ini, penulis akan memperjelas identitas kepercayaan masyarakat adat terhadap kepercayaan mereka sendiri, khususnya kepercayaan Đạo Mẫu masyarakat Vietnam. Penelitian ini juga berfokus pada paham ketuhanan dalam kepercayaan adat Đạo Mẫu. Dengan menggunakan metode studi literatur, penulis menelusuri sumber informasi resmi melalui buku, artikel, dan lain-lain untuk memberikan gambaran tentang kepercayaan Đạo Mẫu. Secara khusus artikel ini akan memaparkan asal mula terbentuknya kepercayaan Đạo Mẫu dan juga menyebutkan sistem ketuhanan dalam kepercayaan Đạo Mẫu. Selain itu, penulis menyajikan keunikan ritual-ritual dalam kepercayaan Đạo Mẫu, serta makna dari ritual-ritual tersebut. Terakhir, peneliti akan memaparkan pandangan pandangan dan peran Dewi Ibu dalam Kepercayaan Đạo Mẫu.